Prioritizing and selecting likely novel miRNAs from NGS data - Backes, Christina; Meder, Benjamin; Heilmeier, Britta; Haas, Jan (Nucleic acids research, 2016)
Abstract. Small non-coding RNAs play a key role in many physiological and pathological processes. Since 2004, miRNA sequences have been catalogued in miRBase,